Efeito do suco de uva (vitis labrusca, bordô) sobre indicadores fisiopatológicos e bioquímicos da síndrome aguda da radiação em ratos wistar - Andrade, Edson Ramos de (2010)
Exposure to radiation has toxic effects and for this reason research on food or drugs with positive radiomodifying action (protective) is of outmost interest to Public Health and Consumer Protection. Thus, the aim of this study was testing the prospect grape juice (Vitis labrusca) as a positive radiomodifier of biological effects that characterize the Acute Radiation Syndrome (ARS). Sixteen male Wistar rats divided into four groups were used, where two groups are acutelly whole body X-irradiated and two were sham X-irradiated with a 200 kV X-rays machine specially designed for biological samples at the University of Leon, Spain. The rats received 10 ml of grape juice or placebo (isocaloric solution of glucose and fructose) to be consumed ad libitum one week before and two weeks after 6 Gy Xirradiation, when they were euthanasiated. Physiopathological, biomolecular and biochemical indications of ARS (anorexia, body weight and major organs, hematological parameters, and indicators of oxidative metabolism) were evaluated and compared with respect to the gastrointestinal system (liver). Results were in agreement with our hypotesis about a potential positive radiomodifier effect of grape juice intake against ARS.